Age‐Specific Vascular Risk Factor Profiles According to Stroke Subtype. Issue 5 (8th May 2017) - Hauer, Allard J.; Ruigrok, Ynte M.; Algra, Ale; van Dijk, Ewoud J.; Koudstaal, Peter J.; Luijckx, Gert‐Jan; Nederkoorn, Paul J.; van Oostenbrugge, Robert J.; Visser, Marieke C.; Wermer, Marieke J.; Kappelle, L. Jaap; Klijn, Catharina J. M.; et al.
Abstract : Background: Ischemic and hemorrhagic stroke are increasingly recognized as heterogeneous diseases with distinct subtypes and etiologies. Information on variation in distribution of vascular risk factors according to age in stroke subtypes is limited. We investigated the prevalence of vascular risk factors in stroke subtypes in relation to age. Methods and Results: We studied a prospective multicenter university hospital–based cohort of 4033 patients. For patients with ischemic stroke caused by large artery atherosclerosis, small vessel disease, or cardioembolism and for patients with spontaneous intracerebral hemorrhage or aneurysmal subarachnoid hemorrhage, we calculated prevalences of vascular risk factors in 4 age groups: <55, 55 to 65, 65 to 75, and ≥75 years, and mean differences with 95% CIs in relation to the reference age group. Patients aged <55 years were significantly more often of non‐white origin (in particular in spontaneous intracerebral hemorrhage and aneurysmal subarachnoid hemorrhage patients) and most often smoked (most prominent for aneurysmal subarachnoid hemorrhage patients). Patients aged <55 years with ischemic stroke caused by large artery atherosclerosis or small vessel disease more often had hypertension, hyperlipidemia, and diabetes mellitus than patients with ischemic stroke of cardiac origin. Overall, the frequency of hypertension, hyperlipidemia, and diabetes mellitus increased with age among all stroke subtypes, whereas smoking decreased with age. Regardless of age, accumulation of potentially modifiable risk factors was most pronounced in patients with ischemic stroke caused by large artery atherosclerosis or small vessel disease. Conclusions: The prevalence of common cardiovascular risk factors shows different age‐specific patterns among various stroke subtypes. Recognition of these patterns may guide tailored stroke prevention efforts aimed at specific risk groups.